If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(x + 12) + 9 = -7 Reorder the terms: -4(12 + x) + 9 = -7 (12 * -4 + x * -4) + 9 = -7 (-48 + -4x) + 9 = -7 Reorder the terms: -48 + 9 + -4x = -7 Combine like terms: -48 + 9 = -39 -39 + -4x = -7 Solving -39 + -4x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '39' to each side of the equation. -39 + 39 + -4x = -7 + 39 Combine like terms: -39 + 39 = 0 0 + -4x = -7 + 39 -4x = -7 + 39 Combine like terms: -7 + 39 = 32 -4x = 32 Divide each side by '-4'. x = -8 Simplifying x = -8
| 16*x=64 | | p(x)=x^4-3x^3+18x^2-48x+32 | | -53-7x=55+2x | | 2x-39+-4x=3 | | 4t-5t=3 | | -42+9x=x+86 | | 4x+19=83 | | 5u-6=-21 | | 3(x+41)+8=50 | | 3.8r=-6 | | -29+6x=31+11x | | -2x-47+4x=-21 | | (x+14)(x-2)= | | 10x-45+12x=43 | | 3r(4r-5)=6(5r+8) | | -3y+10x=-5 | | P=11*3 | | -23-3x=-5x+15 | | 8(x+-44)+-6=34 | | -83-12x=7x+183 | | 2(2x-1)-10=-2(1-x) | | -7(x+-37)+-8=-36 | | 2x^2+6xy-9y^2=x+2y | | -63+3x=7x+21 | | 3p^2=3p | | 3(4z-2x)= | | 4x=7x-33 | | 3(x+13)+4=-23 | | 7x-55=x+35 | | -10(x+33)+-8=-28 | | b+6=-2b+1 | | S*6-39=27 |